A Randomized comparative crossover study to assess the affect on circuit life of varying pre-dilution volume associated with CVVH and CVVHDF - Davies, Hugh; Leslie, Gavin; Pereira, Sandra; Webb, S. (Wichtig Editore, 2008)
To Determine if circuit life is influenced by a higher pre-dilution volume used in CVVH when compared with a lower pre-dilution volume approach in CVVHDF.Pre-diluted CVVHDF appeared to have a longer circuit life when compared to high volume pre-diluted CVVH. The choice of CRRT mode may be an important independent determinant of circuit life.